2020
DOI: 10.3892/etm.2020.8565
|View full text |Cite
|
Sign up to set email alerts
|

DNA‑methylated gene markers for colorectal cancer in TCGA database

Abstract: Colorectal cancer (CRC) is characterized by the accumulation of genetic and epigenetic alterations in neoplastic processes. DNA methylation, as an important epigenetic process, contributes to the development of CRC. In the present study, the epigenetic landscape of genes in CRC was characterized by analyzing the dataset from The Cancer Genome Atlas database and 177 DNA-methylated genes were screened based on the criterion of the Pearson correlation (R) between expression and methylation levels being >0.4. Path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…ZNF proteins, such as ZNF346, ZNF638, and ZNF768, are used as capture antigens in CRC to detect autoantibodies [ 38 ]. Furthermore, in a previous study, epigenetically activated ZNF726 was identified as a prognosis‑associated gene for CRC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZNF proteins, such as ZNF346, ZNF638, and ZNF768, are used as capture antigens in CRC to detect autoantibodies [ 38 ]. Furthermore, in a previous study, epigenetically activated ZNF726 was identified as a prognosis‑associated gene for CRC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modification refers to the heritable changes that do not directly affect the DNA sequence per se , but rather its accessibility and chromatin structure, attributed to incidences of DNA methylation and histone modifications that lead to the dysregulation of gene expression [ 171 ]. In colon cancer, dysregulation that elicits genomic instability causing tumor initiation can derive from gene promoter CpG island methylation as observed in tumor-suppressors Krüeppel-like factor 6 (KLF6), KLF4, and zinc finger protein 726 (ZNF726) silencing; through direct hypermethylation of one allele demonstrated in human mutL homolog 1 (hMLH1) and cyclin-dependent kinase inhibitor 2A (CDKN2A); and through DNA hypomethylation such as in the case of LINC00460 that promotes metastasis [ 172 , 173 , 174 , 175 ].…”
Section: Classical Mechanisms Of Resistancementioning
confidence: 99%
“…Here we have found that epigenetic silencing of ZNF135 is a key feature of stage-IV CRC. It is interesting that another member of the zinc-nger protein family, ZNF726, has been recently identi ed as the only methylated gene signi cantly associated with OS in patients with CRC, without regard for pathologic stage [63]. FAM123A, also known as AMER2, is associated with microtubule proteins [64], and is a paralog of the well-documented FAM123B, a tumor-suppressor whose loss-of-function by mutation, methylation and copy-number aberrations is known to play a pivotal role in colorectal cancer, especially in older patients [65,66,67].…”
Section: Discussionmentioning
confidence: 99%